HIV-1 Vpu blocks recycling and biosynthetic transport of the intrinsic immunity factor CD317/tetherin to overcome the virion release restriction - Schmidt, Sarah; Fritz, Joëlle; Bitzegeio, Julia; Fackler, Oliver Till; Keppler, Oliver Till (mBio, 2011)
The intrinsic immunity factor CD317 (BST-2/HM1.24/tetherin) imposes a barrier to HIV-1 release at the cell surface that can be overcome by the viral protein Vpu. Expression of Vpu results in a reduction of CD317 surface levels; however, the mechanism of this Vpu activity and its contribution to the virological antagonism are incompletely understood. Here, we characterized the influence of Vpu on major CD317 trafficking pathways using quantitative antibody-based endocytosis and recycling assays as well as a microinjection/microscopy-based kinetic de novo expression approach. We report that HIV-1 Vpu inhibited both the anterograde transport of newly synthesized CD317 and the recycling of CD317 to the cell surface, while the kinetics of CD317 endocytosis remained unaffected. Vpu trapped trafficking CD317 molecules at the trans-Golgi network, where the two molecules colocalized. The subversion of both CD317 transport pathways was dependent on the highly conserved diserine S52/S56 motif of Vpu; however, it did not require recruitment of the diserine motif interactor and substrate adaptor of the SCF-E3 ubiquitin ligase complex, β-TrCP. Treatment of cells with the malaria drug primaquine resulted in a CD317 trafficking defect that mirrored that induced by Vpu. Importantly, primaquine could functionally replace Vpu as a CD317 antagonist and rescue HIV-1 particle release.